Climate Change and Capitalism - Park, Jonathan T (Consilience, 2015)
Capitalism was designed as a mechanism for efficiently allocating scarce resources, encouraging human ingenuity, and improving the quality of life for those willing and able to participate in the system. This economic model has been prodigiously effective at enabling people to convert natural resources into fungible commodities and monetary wealth. By transmuting vast amounts of natural resources into marketable products, capitalism has generated an unparalleled degree of wealth and prosperity. In theory, the production of wealth and the collective quality of life can be constantly enhanced under this economic model. Although wealth accumulation has hitherto entailed the unsustainable depletion of natural resources, capitalism maintains that when a commercially viable resource is exhausted, the market will produce an alternative. Thus, capitalism is supposedly an indefatigable method for perpetually generating more wealth and greater social prosperity.